KONFLIK TOKOH UTAMA DALAM NOVEL DEAR NATHAN KARYA ERISCA FEBRIANI: KAJIAN PSIKOLOGI SASTRA - Fahmi, Nurul; Syam, Christanto; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe general problem of this research is the conflict analysis of the main character in the novel Dear Nathan by Erisca Febriani tells the story of a child with all kinds of problems he faces both internal conflicts and external conflicts in his family and also his school environment.The problems in this study were: (1) the main conflict of the main character, (2) the external conflict of the main character, (3) the implementation of literary learning about internal and external conflicts. The purpose of this study was to describe the internal conflict and external conflict of the main character. This study uses a description method with qualitative research. The data from this study are sentences that indicate the internal and external conflicts of the main character. The technique used in this study is documentary study, and the data collection tool is the researcher itself as a key instrument. Based on the results of data analysis there are 58 internal conflict data and 8 external conflict data.Â Keywords: conflict. character, novelÂ